2012
DOI: 10.5539/ass.v8n9p32
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Organizational Citizenship Behavior and Counterproductive Work Behavior

Abstract: Job performance is the most researched concept studied in industrial and organizational psychology, with the emphasis being on organizational citizenship behavior (OCB) and counterproductive work behavior (CWB) as two dimensions of it. The relationship between these two dimensions of job performance are unclear, hence the objective of the current study was to examine the relationship between organizational citizenship behavior and counterproductive work behavior. A total of 267 students studying psychology wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…Thus, female teachers are having more propensities in helping their organization apart from their prescribed duties. These results are also in line with the results of Hafidz et al (2012), who inferred that females exhibit more OCB. Organizational commitment and OCB is more in female teachers as additional duty to assist students because of the reason that the spirit of empathy, altruism, gregariousness, cooperation, and interpersonal orientation has been reported to be of higher level in females.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, female teachers are having more propensities in helping their organization apart from their prescribed duties. These results are also in line with the results of Hafidz et al (2012), who inferred that females exhibit more OCB. Organizational commitment and OCB is more in female teachers as additional duty to assist students because of the reason that the spirit of empathy, altruism, gregariousness, cooperation, and interpersonal orientation has been reported to be of higher level in females.…”
Section: Discussionsupporting
confidence: 91%
“…The current perspective indicated the adoption of both OCB and CWB at an average rate among the staff of every organization. Wahyu Ariani et al and Hafidz [72,73] reported there was a reverse average relationship between OCB and CWB, and thus it seems these behaviors are separately structured, but are related to each other in some way or another.…”
Section: Discussionmentioning
confidence: 98%
“…CWB intends non-forced behaviour that violates significant organizational norms, putting at stake the well-being of its members (Robinson & Bennett, 1995; see also Sackett et al, 2006), or voluntarily harming the organization (Rotundo & Sackett, 2002). Consistent with the model represented in Figure 1, CWB can be regarded as negative or dysfunctional forms of OCB (see Sims & Lorenzi, 1992), but needs not necessarily be considered its orthogonal measure of organizational competition (see Hafidz et al, 2012). In a meta-analysis, Dalal (2005) reported a modest negative relationship (p = −.32) between CWB and OCB.…”
Section: Organizational Citizenship Behaviourmentioning
confidence: 93%